Transmission Loss Allocation Based on Lines Current Flow - Rahmat Aazami; Ali mansori; NosratAllah Mohammad Baigi; Amin Omidian; Ehsan Mohammadian (Institute of Advanced Engineering and Science, 2012)
In this paper, the transmission loss allocation problem has been studied and a new method for loss allocation in pool electricity markets has been proposed. To do that, at first using a transmission line loss equations respect to bus injected currents, the share of each bus from the mentioned transmission line losses has been determined. Then, this method has been applied to the total network transmission lines and the share of each bus from the total losses has been acquired. The proposed method is based on the main network relations and no any simplifying suppose has been used. Finally, the proposed method is studied on a typical network.